Dynamic vulnerability in the pursuit of just adaptation processes: A Boston case study. Issue 94 (April 2019) - van den Berg, Hanne J.; Keenan, Jesse M.
Highlights: Procedural justice requires dynamic assessment of vulnerability. Procedural justice also requires meaningful, inclusive community engagement. Boston's resilience planning leaves room for improvement on procedural justice. Abstract: This article argues that the justness and the efficacy of adaptation processes are dependent on how and when planning actors measure vulnerability and define vulnerable populations. Through a review of climate adaptation and disaster risk reduction literature, this article takes the position that the advancement of procedurally just adaptive planning should engage a dynamic framing of vulnerability that brings together aspects of both contextual and outcome vulnerability in order to support ongoing adaptation planning efforts that include the acknowledgement and representation of a full range of stakeholders. To illustrate this position, a case study of the City of Boston's resilience plans is presented to explore the strengths and weaknesses of current planning practices that vary in their static and dynamic conceptualization of vulnerability and participatory planning processes. This article opens the door for future research that evaluates the procedural justness of adaptation planning processes that are challenged to balance vulnerability assessment methodologies and engagement processes within the context of dynamic social, economic, environmental change.